EVALUATION OF CAPD AS RENAL REPLACEMENT THERAPY IN CHILDREN - Prasetyo, Risky Vitria; Ramadhani, Noershanti; Soemyarso, Ninik Asmaningsih; Noer, Mohammad Sjaifullah (Indonesian Urological Association, 2012)
Objective: To evaluate the outcome of pediatric patients treated with continuous ambulatory peritoneal dialysis (CAPD) performed by experienced pediatric urologists. Material & Method: A retrospective study of children with end-stage renal disease (ESRD) by peritoneal dialysis (PD) in Division of Nephrology Department of Child Health, Faculty of Medicine Airlangga University, Soetomo Hospital, Surabaya, from January 2003 to February 2012 was conducted. Children with acute kidney injury treated by PD were excluded.Data reviewed were age, sex, primary renal disease, age at start of CAPD, duration of CAPD, outcome and cause of death. Descriptive statistics were used to analyze the data.Results: Twenty seven cases of children with CAPD within 9-year period were included. Most patients were 11-15 years old with 62,9% being male. Chronic glomerulonephritis and nephrotic syndrome were the main primary renal diseases. Fifteen (55,6%) patients had peritonitis. The longest duration on CAPD was 53 months. Outcome of 27 children was as follows, 11 patients died (40,8%), 8 patients survived (29,6%), and another 8 were lost to follow-up (29,6%). All (100%) patients had cardiovascular abnormalities as cause of death. Conclusion: The outcome and mortality rate of children with CAPD remain unfavourable. This is a challenge still to be overcomed. Keywords: Continuous ambulatory peritoneal dialysis, children, outcome.